Clinical and Immunological Evaluation of the Effectiveness of Non-Penetrating Deep Sclerectomy in the Early Postoperative Period - S. I. Kolesnikov (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
Today the mechanisms of pathological scarring and inconsistency of the intraocular fluid outflow pathways after nonpenetrating deep sclerectomy (NPDS), reducing its effectiveness, have not yet been determined. There is no systematic information about the regulatory role of cytokine TGF-β and MMP-9 in the mechanisms of formation of the newly created intraocular fluid outflow pathways.Aim: to assess changes in the clinical and immunological status of patients with open-angle glaucoma after NPDS in the early postoperative period.Methods. A prospective examination of 26 patients with open-angle glaucoma before and in 1 month after NPDS with determination of concentration of TGF-β and MMP-9 in tear humor. One month after NPDS, all patients were divided into two groups depending on the effect of the operation achieved according to the developed criteria.Results. Before the operation, tears TGF-β values in group 1 exceeded baseline values of group 2 by 1.4 times, the initial content of MMP-9 in tears in both groups was comparable. After the operation, in group 1, a moderate increase in the concentration of tears TGF-β by 1.3 times and a significant increase in the concentration of tears MMP-9 in 4.6 times compared with baseline values were revealed. In patients of group 2, after NPDS, there was a significant increase in the concentration of tears TGF-β, on average, 2.4 times relative to preoperative values, the content of MMP-9 did not significantly change.Conclusion. 1 month after NPDS, an imbalance in the concentration of TGF-β and MMP-9 in tears was detected in patients of the two groups that have fundamental clinical differences in the hypotensive effect and the formation of postoperative intraocular fluid outflow pathways.